Status Kesehatan Periodontal Pada Pengguna Kontrasepsi Oral, Suntik Dan Implan (Tinjauan Pada Akseptor Kb Di Puskesmas Kebonarum Kabupaten Klaten) - Syamila, Izzah Dina, drg. Edi Karyadi, M.M, drg. Naviatullaily Yarsiska (2016)
Contraception is a method to prevent an unfertilized egg by a sperm that can prevent pregnancy. Contraception method most widely use in Indonesia is a hormonal contraceptive, namely oral, injections, and implants constraseptive. The use of contraceptives containing estrogen and progesterone may affect periodontal health status that can lead to periodontal diseases occur such as gingivitis and periodontitis. The purpose of this study was to determine the effect of oral, injections, and implants constraseptives to periodontal health status on Acceptor Kb in Puskesmas Kebonarum Kabupaten Klaten. The study used observational analytic method with cross sectional approach. Respondents are acceptors aged 20-35 years in the district of Klaten district Kebonarum. This research conducted on 27-31Mei 2016. Technique sampling of this study used purposive sampling. Respondents were asked about their contraceptive use, then the course of the examination was if the respondents agree they can signed informed consent. Examination in this study was Oral Hygiene Index (OHI), plaque index, gingival index and periodontal chart put into PDI scores (Periodontal Disease Index) to determine periodontal health status of respondents. After examination it will show the results. This study was tested using chi square test and obtained the value p = 0.002 (p <0.05) so that it can be conclude that effect of oral, injections and implants contraceptives to periodontal health status on acceptor KB in Puskesmas Kebonarum Kabupaten Klaten.